2020
DOI: 10.1017/s0960258520000288
|View full text |Cite
|
Sign up to set email alerts
|

Field burn versus fire-related cues: germination from the soil seed bank of a South American temperate grassland

Abstract: Fire and grazing are large-scale disturbances that shape the structure and function of open habitats. In temperate grasslands of southern South America, fire is used as a management tool to control tussock grasses and improve forage quality. In this study, we examined if fire and two of its components (heat and smoke) affect germination from the soil seed bank of a temperate grassland in Uruguay. Soil samples were extracted from a recently burned site and from an adjacent area that had not been burned for at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
2
13
0
2
Order By: Relevance
“…The other process is mediated by differences in spatial colonization, a sort of rescue effect (Brown & Kodric‐Brown, 1977). Fire removes above‐ground biomass of competitively dominant species, and bare soil patches are colonized through vegetative propagation from neighboring sites, by germination of a bank or seed rain, or through resprouting from a bud bank (López‐Mársico et al, 2019; Cuello et al, 2020). These multiple colonization events could explain various spatial dynamics in patches of the same burning age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other process is mediated by differences in spatial colonization, a sort of rescue effect (Brown & Kodric‐Brown, 1977). Fire removes above‐ground biomass of competitively dominant species, and bare soil patches are colonized through vegetative propagation from neighboring sites, by germination of a bank or seed rain, or through resprouting from a bud bank (López‐Mársico et al, 2019; Cuello et al, 2020). These multiple colonization events could explain various spatial dynamics in patches of the same burning age.…”
Section: Discussionmentioning
confidence: 99%
“…However, fire effects have been poorly studied in these areas. In grasslands of the geomorphological region Eastern Hills (Sierras del Este), field burns can enhance the forage quality of the tussock grass Saccharum angustifolium (Panicoideae) and reduce its coverage (Royo Pallarés et al, 2005) creating open spaces prone to colonization by other species that propagate vegetatively or by seeds (López‐Mársico et al, 2019; Cuello et al, 2020). In addition, it has been observed that the canopy of Saccharum angustifolium can reduce the incidence of light reaching the lower plant stratum by up to 83% (López‐Mársico et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is common practice to apply either smoke alone or heat alone when assessing fire response in germination studies (Moreira et al 2010, Carthey et al 2018). However, this is both unrealistic and likely insufficient for assessing fire-response, as only smoke and heat combined are likely comparable to the effects of an actual fire on germination (Cuello et al 2020). Within-species variation in response to fire cues may also occur.…”
Section: Discussionmentioning
confidence: 99%
“…For 39 species, we had sufficient seed to assess all treatment combinations but there was insufficient seed to apply all treatments to the remaining 16 species (full details in Appendix S1: Table S2). In these cases, either smoke and heat combined or smoke alone was applied, as these treatments are the most ecologically relevant to in situ fire (Cuello et al 2020). Untreated controls were conducted for all species.…”
Section: Germination Trialmentioning
confidence: 99%
“…Soon after fire, the tussocks begin to produce fresh green leaves, which are attractive and consumed by livestock (Laterra et al 1998;Laterra et al 2003;López-Mársico et al 2021). Also, fire generates bare soil spaces that are quickly occupied by a large number of species found in the regional species pool, but poorly represented before fire (Laterra et al 1998;Overbeck et al 2005;Fidelis et al 2012;Beal-Neves et al 2020;Cuello et al 2020;López-Mársico et al 2021), such as rosette forbs Fidelis et al 2012). Specifically in the Flooding Pampa, fire promotes the invasion of exotic species (Laterra 1997;Juan et al 2000;Laterra et al 2003).…”
Section: Introductionmentioning
confidence: 99%